Intranasal abuse of methylphenidate and bupropion: a case report - Erensoy, Habib; Burhanoğlu, Sabri (Journal of Dependence, 2014)
Methylphenidate is a central nervous system stimulant drug that is used for treatment of Attention Deficit Hyperactivity Disorder (ADHD) and bupropion is used for smoking cessation therapy as well as depression treatment. Oral abuse has been reported as a common rout for addiction/ dependency and it is the most reported form of abuse in the literature. In this case, we are going to report the intranasal abuse of methylphenidate and bupropion. Furthermore, off-label use of ethylphenidate, follow-up and its treatment would be explained/ reported.